Efficacy of Higher Gauged Needles or Topical Pre-Cooling for Pain Reduction during Local Anesthesia Injection: A Split-Mouth Randomized Trial - Srikanth Gadicherla; Mihika Mahandwan; Shane Quek Yi Xuan; Kalyana-Chakravarthy Pentapati (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the efficacy of pre-cooling and the use of higher gauged needles in reducing pain during local anesthetic infiltration. Material and Methods: We conducted a split-mouth randomized controlled trial among 70 patients who require bilateral maxillary local anesthetic (LA) injections for dental treatment. After applying the topical anesthetic, each participant received four local anesthetic injections, two on buccal and two palatal sides. At each visit, the participants received one buccal and one palatal infiltration based on the randomization. On the buccal aspect, participants received LA with a 26G needle injection on one side (control) and a 31G needle (test) on the contralateral side. On the Palatal aspect, participants either received LA with a 31G needle on one side (control). In contrast, the opposite side was preceded by topical ice application (iced cotton swab) before LA with a 31G needle (test). Both the visits were spaced with a gap of 7-10 days based on the participants' feasibility. Participants were asked to rate the pain on a visual analog scale independently for buccal and palatal LA injections. Results: On the Buccal aspect, the mean pain scores were 2.74 ± 1.26 and 2.11 ± 1.26 for control and test groups, respectively (p=0.002). On the Palatal aspect, the mean pain scores were 4.14 ± 1.49 and 4.3 ± 1.80 for control and test groups, respectively (p=0.295). Conclusion: Significant lower pain scores were reported with higher gauge needles (31G) when compared to traditional (26G) needles on the buccal aspect. No significant difference was seen with pre-cooling the injection site on the palatal aspect when used with higher gauged needles (31G).